Analysis of the serving motion of male college tennis players in matches - Horiuchi, K; Ae, M.; Numazu, N.; Kawabata, M. (ISBS Proceedings Archive (Michigan), 2022)
The purpose of this study was to analyse and compare the serving motions of the fast hitters who can hit fast-ball in serve and normal Japanese male college players in matches. The variables used in this study were ball speed, racket speed, joint and segment angles of the shoulder, the torso and the limbs. Ball speed and racket speed for the fast hitters were significantly greater than that of the normal players. There were a significant differences between two groups in the angles of the shoulder and the knee joint. To improve the racket speed of the normal players, it is necessary to maintain the shoulder more horizontally abducted, the shank not too lean forward and the torso upright during the backswing, and to reduce the shoulder abduction during the forward swing.